The effects of dietary administration of two sources of β-glucan on growth and physiological activity of common carp: بيتا جلوكان الغذائي كمحفز مناعي لاسماك الكارب الشائع - Alkatrani, Layla; Al-Jumaiee , Shaymaa (Journal of King Abdulaziz University: Marine Sciences, 2023)
A growth experiment has been established to estimate the influence of two diverse sources of β-glucan, fungal derived from baker's yeast Saccharomyces cerevisiae and vegetal derived from barley bran Hordeum vulgare as long-term effect on the growth performance, survival rate, and physiological status in fingerlings of common carp (Cyprinus carpio) after 60 days of feeding on artificial diets containing 3% fungal β-glucan (A group), 3% vegetal β-glucan (B group), as well as 0% β-glucan (C group) as a control in duplicate for each group. Some of the blood parameters such as Packed cell volume PCV, osmotic pressure OP, total protein content TP, glucose content GLU., enzymes of ALP, AST, and ALT were estimated. Results of growth performance including weight increase, growth rates, relative growth rates, and specific growth rates as well as survival rates showed no significant variances (P > 0.05) among the three groups, although there were rises in these values in groups of fungal (A) and vegetal (B) sources of β-glucan additives than the control group C. Contrariwise, most of the physiological parameters estimated in the fish blood showed a significant improvement in performance in group A and then B, where PCV, OP, TP, GLU, ALP, AST, and ALT values showed a significant decline (P < 0.05) for A group and for B group, from the control group C. The study confirmed that the addition of β-glucan, especially that derived from a fungal source to fish diets, led to a non-significant increase in growth and survival rates, while it guided to a significant improvement in the physiological activities of the parameters PCV, OP, TP, GLU, ALP, AST, and ALT in the fish blood. The study encourages the addition of the fungal source of β-glucan to the artificial diets of common carp as Immunostimulator for its health enhancement.